Coagulation activation in young survivors of myocardial infarction (MI) - a population-based case-control study - Brodin, Ellen; Børvik, Trond; Sandset, Per Morten; Bønaa, Kaare H.; Nordøy, Arne; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2004)
Formation of an occlusive thrombus by exposure of tissue factor (TF) to circulating blood and subsequent triggering of coagulation by TF-FVIIa complexes on ruptured atherosclerotic plaques is thought to be a key event in acute MI. Tissue factor pathway inhibitor (TFPI) is a potent inhibitor of TF-induced coagulation by neutralizing FXa and inhibiting the TF-FVIIa complex. A case control study was conducted to investigate the role of coagulation activation in MI. Sixty-two patients with verified MI, 40-60 yrs of age, were recruited into the study and examined 1-4 years after the acute coronary event. Thrombinantithrombin complex (TAT) was significantly increased in MI patients (8.2 ± 12.9 µg/l vs. 3.9 ± 2.6 µg/l, p=0.01). In contrast, FVIIa was lower in MI patients (41 ± 13 mU/ml vs. 48 ± 15 mU/ml, p=0.003) accompanied by an increase in plasma free TFPI antigen (20.9 ± 5.0 ng/ml vs. 19.2 ± 4.9 ng/ml, p=0.03). Significant trends for increase in triglycerides and total cholesterol across quartiles of free TFPI Ag were found in both groups, whereas HDL cholesterol decreased across quartiles of TFPI among control subjects. The compensatory increase in plasma free TFPI with established lipid and haemostatic risk factors were abrogated in the MI patients. An apparent increase in the basal activation of the coagulation system was observed in young patients with MI. Enhanced coagulation activation was accompanied by a decrease in FVIIa and increase in free TFPI Ag, probably reflecting a modest triggering of TF-induced coagulation in these patients.
Keywords: Tissue factor pathway inhibitor (TFPI); tissue factor / factor VII; ischaemic heart disease; thrombin